Epidemiology of snakebites in Kédougou region (eastern Senegal): comparison of various methods for assessment of incidence and mortality. Issue 1 (December 2016) - Lam, Absa; Camara, Bouna; Kane, Oumar; Diouf, Amadou; Chippaux, Jean-Philippe
Abstract Background Although considered a public health issue in Senegal, the actual incidence and mortality from snakebite are not known. In the present study, an epidemiological survey was carried out in Kédougou region, southeastern Senegal, where envenomations, particularly byEchisocellatus, are frequent and severe. Methods Three sources of data were used: records from health centers and reports by health professionals; traditional healers; and household surveys. Results The annual incidence and mortality provided by health centers were 24.4 envenomations and 0.24 deaths per 100, 000 population, respectively. The annual incidence recorded by traditional healers was 250 bites per 100, 000 inhabitants, but the number of deaths was unknown. Finally, the household surveys reported an annual incidence of 92.8 bites per 100, 000 inhabitants and an annual mortality rate of 2.2 deaths per 100, 000 inhabitants. The differences in incidence and mortality between the different methods were explained by significant bias, resulting in particular from the complex patient's healthcare-seeking behavior. The incidence provided by health records should be used to specify the immediate quantitative requirements of antivenoms and places where they should be available first. Conclusion Mandatory reporting of cases would improve the management of envenomation by simplifying epidemiological surveys. Patients' preference for traditional medicine should prompt health authorities to urge traditional healers to refer patients to health centers according to defined clinical criteria (mainly edema and bleeding or neurotoxic symptoms). Finally, household surveys were likely to reflect the actual epidemiological situation. Poison Control Center of Senegal should continue its work to sensitize stakeholders and train health staff.